MOLECULAR IDENTIFICATION OF YEAST OF THE PULQUE BY PCR-DGGE, A TRADITIONAL MEXICANBEVERAGE - J., Marcial-Quino; B., Garcia-Ocón; J.A., Mendoza-Espinoza; S., Gómez-Manzo; E, Sierra-Palacios (International Journal of Research -GRANTHAALAYAH, 2015)
Currently it is well known that yeasts play an essential role in the production of different beverages. In this paper, were identified some of the yeasts involved in the fermentation process of the pulque, a Mexican traditional beverage. Samples were collected from different regions of Mexico and yeasts were detected directly from samples without cultivation. Identifying the yeasts was obtained using amplification the D1/D2 domain of the 26S rRNA gene and Denaturing Gradient Gel Electrophoresis (DGGE). The results of DGGE showed different profiles of bands in each of the analyzed samples, indicating the presence of several species of yeast, which was also confirmed by sequencing of the bands corresponding to the domain D1/D2, succeeded in identifying five species of yeasts. The results obtained in this work demonstrated that the technique used for identification of yeasts of pulque was efficient. Besides, the optimization of this method could also allow rapid identification of yeasts and help understand the role of these in the fermentation process of this beverage, as well as the isolation of strains of interest for biotechnological purposes such as production of ethanol or metabolites with nutraceutical activity.